PENGARUH HARGA, BRAND IMAGE, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA KONSUMEN ARTFRESH - sahrur cahya ramadhan; Ignatius Teodore Teddy Saputra (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
The perfume or fragrance business experienced positive growth as seen from the world's perfume exports which experienced a significant increase every year. The existence of this phenomenon is certainly a good opportunity for Artfresh which is a business engaged in the perfume sector in Surabaya. This study aims to determine the effect of price, brand image, and service quality on purchasing decisions on Artfresh consumers. This study uses a quantitative approach using purposive sampling technique. Samoel used in this study as many as 90 respondents. The data collection method uses a questionnaire method that uses a Likert Scale score of 1-5 with multiple linear regression analysis methods with SPSS tools. The results of this study indicate that price has a significant effect on purchasing decisions, brand image does not significantly affect purchasing decisions, service quality has a significant effect on purchasing decisions.